The role of proprioception in shoulder disease - Di Giacomo, G.; Ellenbecker, T. (Medicine and Science in Tennis, 2009)
The purpose of this article will be to review the proprioceptive mechanisms of the human shoulder and how it relates to shoulder injury relevant for the evaluation and treatment of the elite tennis player.